The Impact of the US-China Trade War on the Motivation for Expansion in the Electron-ic Manufacturing Sector in Sichuan - Jingying Fu; Jacky Mong Kwan Watt (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The abstract examines the impact of the US-China Trade War on the motivation for expansion within Sichuan's electronic manufacturing sector. The trade conflict has introduced significant challenges, including increased tariffs and supply chain disruptions, compelling local firms to reassess their strategies. In response, companies have intensified their focus on innovation and technological advancement to enhance competitiveness and reduce reliance on foreign technologies. This drive for self-sufficiency has led to increased investment in research and development, fostering new capabilities and market opportunities. Moreover, the trade war has shifted attention toward domestic markets, prompting firms to diversify their supply chains and explore alternative business avenues. Government support has further facilitated this expansion, providing resources and incentives that bolster growth. The findings suggest that the motivations for expansion are closely intertwined with the broader geopolitical landscape, shaping the future of Sichuan's electronic manufacturing industry, based on insights gathered from a sample of 380 Sichuan electronic manufacturer operators in the study.